Physicochemical properties and adaptability of amine-producing Enterobacteriaceae isolated from traditional Chinese fermented fish (Suan yu). (1st February 2022) - Meng, Ju; Yang, Qin; Wan, Weiyang; Zhu, Qiujin; Zeng, Xuefeng
Highlights: Amine-producing E. coli was isolated and identified from Suan yu. The physical and chemical factors on amine production were discussed in Suan yu. The changes in BA type and content in inoculated fermented surimi were monitored. Abstract: The formation of biogenic amines (BAs) is an important potential danger in traditional fermented fish (Suan yu), and Enterobacteriaceae play an important role in the formation of BAs. The amine production abilities of 97 strains of Enterobacteriaceae screened from traditional fermented Suan yu were analyzed by reversed-phased high-performance liquid chromatography (HPLC). The genotypic diversity of amino acid decarboxylase on 23 strains of high-yield BAs was verified by PCR. Enterobacteriaceae with the highest production of amines was determined by analysis of the effects of physicochemical factors (pH, NaCl, temperature, and aerobic/anaerobic) on BA production and principal component analysis (PCA). The adaptability of the strains was examined using surimi simulation fermentation system, and the correlations among the indicators were analyzed using Cytoscape. Results showed that 97 strains of Enterobacteriaceae had strong amine-producing ability. Furthermore, 23 strains producing high yields of putrescine, cadaverine, and histamine were identified. All of the strains carried Idc, odc, speA, speB, and adiA, and five strains carried hdc . pH mainly affected the BA production of amine-producing bacteria. Three strains ( Enterobacter asburiae 26C3, Klebsiella pneumoniae 47C2, and Morganella morganii 45C3) had the best amine-producing ability and used as the inoculated group. In this group, the values of BA (228.70–290.05 mg/kg) and the total volatile base nitrogen (TVB-N, 173.87–221.87 mg/100 g) exceeded the limit. Moreover, myofibrillar protein degradation was significant as indicated by the sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis and decreased FAA content. Cytoscape software and principal component analysis (PCA) indicated that Enterobacteriaceae and pH were related to BA formation in Suan yu. These results provide a theoretical basis for controlling the BA of fermented fish products.